Motion Interference Inspection and Workspace Research of 3-RRR Spherical Parallel Robot - Li Wang; Rong Wang (Jixie chuandong)
The 3-RRR spherical parallel robot is applied as the actuator for spatial positioning and tracking，the Euler angle is described the pose of the robot end moving platform. The robot position equation is established，and the expression of joint angle is obtained. The necessary conditions of the robot have space and the structural constraints that each joint must satisfy are given by means of geometric analysis. The connecting rod of spherical mechanism is represented as a large circular arc on the spherical surface. The motion interference of the connecting rod is shown as the intersection of two connecting rod arcs. The spatial arc representing the connecting rod is mapped to a plane curve by using the method of spherical pole mapping. The problem of finding the intersection point of spatial circular arc is simplified to the intersection of plane curve. At the same time，considering the actual situation that the parallel robot has multiple positions in each posture of the moving platform and each link has two sides of the boundary. The criterion and process of identifying the kinematic interference of the parallel robot is proposed. In the example，the attitude space of the robot is explored by taking the kinematics solution of each branch of the robot satisfying the constraint conditions of joint structure as the target，and the motion interference discrimination of each point in the attitude space is further carried out，and the distribution of the motion interference of the linkage in the attitude space is obtained.